Supplemental Material: Linking lava morphologies to effusion rates for the 2014–2015 Holuhraun lava flow field, Iceland - Joana R. C. Voigt (11384513); (281964) (2021)
Details about previous established links between emplacement conditions and lava types, data and methods, additional correlation results, and limitations.